Caryā of Padasādhana – A Vajrayāna Ritual (SIRJANĀ – A Journal Of Arts and Art Education, 2021)
Padasādhana ritual or caryā is an alphabet of vajrayāna religion represented by twenty eight caryāgīti forming a major structure of the ritual performed. All the caryāgīti enacted during the ceremony is a climbing of steps one by one culminating in vajrapada. Construction of maņđala, utterance of mantra and formation of mudra in course of worships are the pillars on which edifice of salvation is built. All the worships are based on maņđala, mudra and mantra. What transpires for spiritual emancipation is through gītī or song and nŗtya or dance which is meant for visualization and ultimate realization of the set goal of the vajrayāna religion that is Buddhahood or Nirvāņa.